The influence of school environment and the performance of the honorary teachers of Islamic education toward the learning achievements - Milya Angreranti; Noor Malihah (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2017)
This research aims to know the influence of school environment and the performance of the honorary teachersof Islamic Education inSD Negeri Jetis I and SD Negeri Nampu I Karangrayung toward the students’ learning achievements. The study as designed as a research survey using quantitative methods (implementing partial regression or double recreation). The respondents are the fifth-grade students of SD Negeri Jetis I and SD Negeri Nampu I Karangrayung. The findings show that (1) there is a positive influence of school environment in SD Negeri Jetis I and SD Negeri Nampu I Karangrayung toward the students’ learning achievement as much as 2.7%. It means if the school environment is increased by one point then the students’ learning achievements will be increased by 2.7%, (2) there is a positive influence on the performance of the honorary teacher Islamic Education in SD Negeri Jetis I and SD Negeri Nampu I Karangrayung toward the students’ learning achievement as much as 13.7%.This means if the performance of the honorary teachersIslamic Education is increased by one point then the students’ learning achievements will be increased by 13.7%, and (3) there is a positive influence of school environment and the performance of the honorary teachersIslamic Education in SD Negeri Jetis I and SD Negeri Nampu I Karangrayung toward students’ learning achievement as much as 13.7%.